Ellis-van Creveld syndrome: A case report - Shah B; Ashok L; Sujatha G (Wolters Kluwer Medknow Publications, 2008)
Ellis-van Creveld syndrome (EvC) is a disease complex, where all the three embryonic layers appear to be involved. This disorder is also called as Chondroectodermal dysplasia. EvC is an autosomal recessive disorder resulting from mutations in these patients. Mutations in the two genes EVC and EVC2, have been identified to cause the condition. It has been considered as a skeletal dysplasia with an incidence of approximately 1 out of 1,50,000 live births. A high prevalence has been reported among certain populations like Amish and Arabs of Gaza strip. There are more than 300 cases of EvC reported into the literature. About 50-60% of cases have been reported with congenital cardiac malformations.